Action Plans in Asthma - Marie-France Beauchesne; Valérie Levert; Miray El Tawil; Manon Labrecque; Lucie Blais (Canadian Respiratory Journal)
BACKGROUND: Action plans are recommended for most patients with persistent asthma to reduce the morbidity associated with this chronic disease. Unfortunately, despite these recommendations, this tool remains underused.